Pre-labor Rupture of Membranes at Term in Patients with an Unfavorable Cervix: Active versus Conservative Management - Aqueela Ayaz; Shazia Saeed; Mian Usman Farooq; Fayaz Ahmad; Luqman Ali Bahoo; Iftikhar Ahmad (Elsevier, 2008)
Objective: To compare the safety and efficacy of conservative management of pre-labor rupture of membranes (PROM) at term in patients with an unfavorable cervix, with active treatment using oral misoprostol. Materials and Methods: This quasi-experimental study was conducted between June 1, 2004 and November 30, 2004 at Bahawal Victoria Hospital, Bahawalpur, Pakistan. Eighty-four multigravid women (parity, < 5) at ≥37 weeks' gestation and with unfavorable cervices were divided equally between group S (study) and group C (conservative). Group S was given 50 μg of oral misoprostol every 4 hours for a maximum of four doses, while group C was managed conservatively. The intervals between PROM and significant uterine contractions and delivery, the mode of delivery, and maternal and fetal/neonatal complications were the main outcome measures. Results: The intervals between PROM and the onset of uterine contractions and delivery were lower in group S than group C (9.6 vs. 14.8 hours; p< 0.001) and (11.6 vs. 17 hours; p < 0.001), respectively. Fewer women delivered abdominally within 24 hours of PROM in group S than in group C (5% vs. 24%; p < 0.05). Induction failure in group S was less than conservative management failure in group C (10% vs. 60%; p < 0.001). The maternal complication rate was less in group S than in group C (7% vs. 14%;p > 0.05), but the fetal/neonatal complication rate was similar in both groups (5%). Conclusion: Oral misoprostol (50 μg) is safe and effective for cervical ripening and labor induction in patients with PROM and an unfavorable cervix. [Taiwan J Obstet Cynecol 2008;47(2):1 92-1 96]